Code-Switching on Tansi Language Spoken by People in Lembah Segar Sub-District - Ega Putri Afilta; Jufrizal Jufrizal (Universitas Negeri Padang, 2022)
People usually choose different codes in different situation in every interaction. The phenomenon of code-switching is common in bilingualism and occurs in conversation. Code-switching occurs when conversation use two languages together to the extent that they change from one language to other in the course of a single utterance. By using qualitative method, this study was aimed to analyze the types and function of code-switching found in the utterance spoken by people in Lembah Segar sub-district. The researcher analyzed sixty three utterance of Minangkabaunese-Tansi language switched spoken by people in Lembah Segar sub-district. Romaine’s (1995) theory is applied in this research to find the types of code-switching. To finding the functions of code-switching the researcher used Gumperz’s (1982) theory. The result of this study shows that the intra-sentential switching was the most common type of code-switching. Also, Interjection was the most function of code-switching used by people in Lembah Segar sub-district. This research gives a contribution in sociolinguistics fields. It is because the result of this study shows the relation of language and society.